CURRENT TRENDS, PROBLEMS AND PROSPECTS OF PARTICIPATION OF AREAS DEVELOPMENT PROJECTS IN THE COMPETITION FOR FUNDING FROM SRDF - Kropelnytska , S.O. (The actual problems of regional economy development, 2016)
The article is devoted to the topic – the financing of areas development projects by the State Regional Development Fund (SRDF). The goal – to identify problems and outline prospects of regional development projects participating in the competition for funding SRDF. The results are to analyze the state of funding and disclosure of problematic aspects of the selection of projects to receive funding SRDF. The novelty – the justification of recommendations for improvement of SRDF activities. The practical significance is reduced to provide specific proposals to address the institutional and financial problems of the SRDF functioning. JEL: R 58